Applicant Reactions to Digital Selection Methods: A Signaling Perspective on Innovativeness and Procedural Justice - Nicholas Folger; Prisca Brosi; Jutta Stumpf-Wollersheim; Isabell M. Welpe (Journal of Business and Psychology, 2021)
Research has shown that the use of digital technologies in the personnel selection process can have both positive and negative effects on applicants' attraction to an organization. We explain this contradiction by specifying its underlying mechanisms. Drawing on signaling theory, we build a conceptual model that applies two different theoretical lenses (instrumental-symbolic framework and justice theory) to suggest that perceptions of innovativeness and procedural justice explain the relationship between an organization's use of digital selection methods and employer attractiveness perceptions. We test our model by utilizing two studies, namely one experimental vignette study among potential applicants (N0.167em=0.167em475) and one retrospective field study among actual job applicants (N0.167em=0.167em335). With the exception of the assessment stage in Study 1, the positive indirect effects found in both studies indicated that applicants perceive digital selection methods to be more innovative. While Study 1 also revealed a negative indirect effect, with potential applicants further perceiving digital selection methods as less fair than less digitalized methods in the interview stage, this effect was not significant for actual job applicants in Study 2. We discuss theoretical implications for the applicant reactions literature and offer recommendations for human resource managers to make use of positive signaling effects while reducing potential negative signaling effects linked to the use of digital selection methods.
Keywords: 650; Digital selection methods; Applicant reactions; Innovativeness; Procedural justice; Employer attractiveness; Signaling theory